Effect of the Nonprestressed/Prestressed BFRP Bar on Flexural Performance of the Bamboo Beam. (9th October 2019) - Lv, Qingfang; Ding, Yi; Liu, Ye
Abstract : Until now, the systematical and comprehensive strengthening techniques have not been formed for the bamboo structure. Under such background, this paper aims to explore the effects of the application of the nonprestressed and prestressed basalt fiber-reinforced polymer (BFRP) bars on the flexural performance of the beams made of the laminated bamboo and reconstituted bamboo materials. Two series of four-point bending tests were thus conducted. In the first series of tests, the pure laminated bamboo beam and the laminated bamboo beam applied with nonprestressed BFRP bar were compared. Test results showed that the ultimate load and deformation capacity of the laminated bamboo beam was improved due to the existence of the BFRP bar. In the second series of tests, the reconstituted bamboo beams applied with nonprestressed and prestressed BFRP bars were compared. It is found that the ultimate load of the reconstituted bamboo beam was not improved by the application of the prestressed force. The further analysis related to the prestress loss demonstrated that the prestress loss before the release of the prestressed BFRP bar could reach up to 31.8–37.3% compared with the design initial prestressed stress. The prestress loss caused by the elastic deformation of the bamboo beam can be neglected. For all tested specimens, the plane section assumption was acceptable and the position of the neutral axis of the beam gradually moved down with the increase of the applied load.